(untitled) (Pedagogical Horizons, 2025)
How can human rights be taught in a way that contributes to respectful coexistence? This article builds a bridge between the fundamentals of human rights education and the phenomenological concept of otherness, and then illustrates the consequences using two teaching examples. It begins with the concept of education about, through and for human rights, as enshrined in the UN Declaration on Human Rights Education and Training (2011). It then contextualises the status quo of the implementation of children’s rights in Austria by examining the problem of anti-democratic educational practices. In a further step, the assertion and enforcement of (legal) claims is outlined as a relational practice and explored in greater depth using the phenomenological concept of ‘otherness’. The practical implementation is then illustrated and systematically explained using two teaching examples. The focus is on the practices of addressing, engaging in democratic discourse, and dealing with justifications for behaviour that violates human rights or fails to promote democracy. Finally, key elements of democratic human rights education are summarised, and limitations and open questions regarding the pedagogical professionalisation of human rights education are highlighted.